Foot Anthropometric Profile of High School Students in Bandung - Imam Ramdhani Abdurrahman; Alwin Tahid; Fathurachman Fathurachman (Faculty of Medicine Universitas Padjadjaran, 2018)
Background: During the process of walking, the foot plays a role in supporting the body weight. Due to continously with stand weight, a person will experience foot pain aggravated by the use of improper shoe size. Foot anthropometric data acts as reference in the manufacture of orthotics and shoes with appropriate size, while Indonesia still does not have foot anthropometric data. The purpose of this study was to describe foot anthropometric data of high school students in Bandung in order to obtain good fitting shoes.Methods: The study was performed using observational descriptive method on 81 students aged 16–18 years from three different senior high schools in different regions of Bandung in November 2014.Results: The mean of foot and ankle anthropometry of senior high school students were 25.75 cm for Foot Length, 18.82 cm for Ball of Foot Length, 21.57 cm for Outside Ball of Foot Length, 9.70 cm for Foot Breadth Diagonal, 5.43 for Heel Breadth, 6.00 cm Navicular Height, 6.62 cm for Instep Height and 5.06 for Heel to Lateral Malleolus.Conclusions: The anthropometric data help the footwear industry to determine the design and size for shoes in Indonesia.